The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5194/soil-2-325-2016
|View full text |Cite
|
Sign up to set email alerts
|

Gone or just out of sight? The apparent disappearance of aromatic litter components in soils

Abstract: Abstract. Uncertainties concerning stabilization of organic compounds in soil limit our basic understanding on soil organic matter (SOM) formation and our ability to model and manage effects of global change on SOM stocks. One controversially debated aspect is the contribution of aromatic litter components, such as lignin and tannins, to stable SOM forms. In the present opinion paper, we summarize and discuss the inconsistencies and propose research options to clear them.Lignin degradation takes place stepwise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 122 publications
2
17
0
Order By: Relevance
“…During potential passage through deeper soil, aquifers, and downstream aquatic systems, these signal become less dominant and NOSC, AI MOD , and DBE of DOM decrease simultaneously with a shift from bi-or multi-modal ion abundance patterns to unimodal ones. Similar losses of aromatic constituents have been described for soils and rivers by other techniques (Creed et al, 2015;Klotzbücher et al, 2016). This implies that freshly decomposing materials can be traced by their contribution of aromatic-and phenolic-type formulae (Roth et al, 2013(Roth et al, , 2014(Roth et al, , 2016Nowak et al, 2017;Schwab et al, 2017).…”
Section: Retrieval Of Discriminating Information and Biogeochemical Tsupporting
confidence: 71%
“…During potential passage through deeper soil, aquifers, and downstream aquatic systems, these signal become less dominant and NOSC, AI MOD , and DBE of DOM decrease simultaneously with a shift from bi-or multi-modal ion abundance patterns to unimodal ones. Similar losses of aromatic constituents have been described for soils and rivers by other techniques (Creed et al, 2015;Klotzbücher et al, 2016). This implies that freshly decomposing materials can be traced by their contribution of aromatic-and phenolic-type formulae (Roth et al, 2013(Roth et al, , 2014(Roth et al, , 2016Nowak et al, 2017;Schwab et al, 2017).…”
Section: Retrieval Of Discriminating Information and Biogeochemical Tsupporting
confidence: 71%
“…Several studies showed that lignin-derived aromatic compounds sorb preferentially to soil minerals due to their high content of carboxyl groups (e.g., summarized in Klotzbücher et al . 37 ). Sanderman et al .…”
Section: Resultsmentioning
confidence: 99%
“…High abundances of this new marker in ground water could indicate fast transport of water and DOM through the subsurface. As aromatic organic matter is known to interact with mineral surfaces, the potential applicability of the proposed molecular markers in groundwater will depend on the mineral structure of the respective subsurface environment (Klotzbücher et al, 2016). Recent investigations show that a considerable proportion of lignin-derived phenols might be irreversibly sorbed to minerals (Kaiser and Guggenberger, 2000;Hernes et al, 2013), thereby limiting the potential traceability of lignin-derived markers into groundwater.…”
Section: Age Correlation Of Molecular Entitiesmentioning
confidence: 99%